Can the relative price ratio of gold to platinum predict the Chinese stock market? - Han, Xing; Ruan, Xinfeng; Tan, Yongxian (2020)
In this paper, we examine whether the relative price ratio of gold to platinum (GP ratio) can predict the aggregate stock market return in the US and China. We confirm that the GP ratio is a strong predictor of US market excess return; however, it is not a reliable predictor for excess return in the Chinese stock market. The evidence highlights the limitation of relying on the GP ratio as a non-parametric, real-time return predictor, and indicates the diversification benefits of investing in the Chinese stock market.